prototype sistem monitoring suhu dan kelembapan pada gedung sarang walet berbasis web - Baharuddin; Fadil, Ahmad (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Advances in science and technology, in principle, can be applied to overcome these problems, namely by making temperature and humidity monitoring devices that work electronically. Temperature and humidity in the swallow house can be detected using a DHT22 sensor, then processed by the ESP32 SIM800L microcontroller and displayed in the form of an output in the form of steam spraying from a steam engine that can turn on and off. This study uses a descriptive research method which provides an overview of what actually happened, while the data collection method used is to observe directly the object of research at the swallow bird house on Jl. H. A. Moh. Arsyad, Soreang District, Parepare City. and the testing carried out is blackbox testing that focuses on the functional requirements of the software. The design method is a prototype. The result of this research is a system that can monitor the conditions of temperature and humidity in the swallow house. The results of testing the design of this tool conclude that the expected functions are all successful as desired.